Color and translucency stability of contemporary resin‐based restorative materials. Issue 6 (14th August 2020) - Sulaiman, Taiseer A.; Rodgers, Brandon; Suliman, Abdulhaq A.; Johnston, William M.
Abstract: Objective: To determine color and translucency stability of present‐day resin‐based restorative materials. Materials and methods: Disk‐shaped (1.0 × 10 mm) resin composites (Filtek Universal, 3M ESPE; Spectra ST, Dentsply Sirona; Gradia Direct X, GC America; Estilite Quick, Tokuyama; Harmonize, Kerr; ACTIVA Bioactive‐Restorative, Pulpdent) were prepared and divided into four staining groups (n = 5); coffee (55°C), grape juice (5°C), deionized water (25°C) and thermocycling (20 000 cycles, 5°C to 55°C with a 30‐second dwell time). Spectrophotometer measurements were taken at baseline and 14 days for each group and the color stability (CIEDE2000) and changes in the translucency parameter (RTPCIEDE2000 ) and luminous transmittance of each composite were determined. A 2‐way analysis of variance (ANOVA) using maximum likelihood estimations was used for analysis for these changes, with subsequent pairwise comparisons using Bonferroni‐corrected Student's t tests and an experiment‐wise α = 0.05. Results: A significant interaction ( P < .0001) between material and treatment was found for each change in the esthetic property tested over 14 days. Multiple significant differences between materials for each treatment and between treatments for each material were identified. Conclusions: The severity of color change and translucency of resin‐based materials are dependent on their type, mostly affected by the coffee staining medium. Nano‐filled resin composite is most resistant to color change and with stable translucency after artificial aging. Clinical Relevance: Nano‐filled resin composite may be the most esthetically durable resin‐ based restorative material. Micro‐hybrid resin composite and resin‐modified glass ionomer restorative material are susceptible to color change and losing their translucency. Hot coffee solution may shorten the esthetic lifespan of a resin‐based material.